Cervical histomorphology of successfully detorted uterine torsion affected buffaloes subjected to intracervical hyaluronidase or PgE1 treatment - SINGH, NAVDEEP; GANDOTRA, V K; GHUMAN, S P S; PATHAK, DEVENDRA; HONPARKHE, M (The Indian Journal of Animal Sciences, 2021)
Twenty-four buffaloes presented between 36-72 h of occurrence of uterine torsion were successfully detorted and equally divided to intracervical hyaluronidase enzyme or prostaglandin E1 (PgE1) treatment or control group for investigating the treatment effectiveness for complete cervical dilatation. Intracervical treatment was administered immediately after detorsion, and cervical biopsy was collected immediately before instituting treatment and at time of cervical dilatation or at 18 h post detorsion in case of non-dilated cervix. The doppler indices of middle uterine artery were evaluated at an hour before detorsion and 0.5 h after detorsion. In control group, none of the buffaloes exhibited cervical dilatation, whereas, 87.5% buffaloes of hyaluronidase group and 62.5% of PgE1 group exhibited cervical dilatation. Following intracervical treatment, lamina propria showed loosely arranged collagen fibres along with hemorrhages, polymorphonuclear (PMN) cells and intercollagen space filled by homogenous/ watery substance in case of dilated cervix. In non-dilated cervix, the collagen fibres were tightly arranged with lesser number of PMN cells and negligible haemorrhages at 18 h after treatment. The doppler indices of the middle uterine artery revealed improvement (P